Linguistic ecology : language change and linguistic imperialism in the Pacific region - Mühlhäusler, Peter (Politics of language., 1996)
In this topical study of the large-scale loss of human language, the author examines the transformation of the Pacific language region. He focuses on cultural and historical forces to explain such loss.